(untitled) (LEARNing Landscapes, 2015)
In this commentary I connect today’s emphasis on collaborative learning with the Nordic tradition of study/research circles and action research. More specifically, I do this by examining three key aspects: the need to understand one’s history and educational roots; the importance of fostering and generating middle leaders through action research; and the significance of recognizing middle leaders in schools and pre-schools for the development of collaborative learning.